Investigating the metabolomic pathways in female reproductive endocrine disorders: a Mendelian randomization study - Lu, Fei-fan; Wang, Zheng; Yang, Qian-qian; Yan, Feng-shang; Xu, Chang; Wang, Ming-tang; Xu, Zhu-jing; Cai, Sheng-yun; Guan, Rui (Frontiers in Endocrinology, 2024)
Introduction: Reproductive endocrine disorders (RED), including polycystic ovary syndrome (PCOS), endometriosis (EMs), and female infertility (FI), significantly affect women's health globally, with varying prevalence across different regions. These conditions can be addressed through medication, surgical interventions, and lifestyle modifications. However, the limited understanding of RED's etiology and the substantial economic burden of its treatment highlight the importance of investigating its pathogenesis. Metabolites play a critical role in metabolic processes and are potentially linked to the development of RED. Despite existing studies suggesting correlations between metabolites and RED, conclusive evidence remains scarce, primarily due to the observational nature of these studies, which are prone to confounding factors.Methods: This study utilized Mendelian Randomization (MR) to explore the causal relationship between metabolites and RED, leveraging genetic variants associated with metabolite levels as instrumental variables to minimize confounding and reverse causality. Data were obtained from the Metabolomics GWAS Server and the IEU OpenGWAS project. Instrumental variables were selected based on their association with the human gut microbiota composition, and the GWAS summary statistics for metabolites, PCOS, EMs, and FI were analyzed. The MR-Egger regression and randomeffects inverse-variance weighted (IVW) methods were employed to validate the causal relationship. Cochran's Q test was employed to evaluate heterogeneity, sensitivity analysis was performed using 设置了格式: 字体: (默认) Times New Roman, (中文) +西文正文 (Calibri) 设置了格式: 字体: (中文) +西文正文 (Calibri) 删除了: and Obstetrics 34 设置了格式: 字体: (默认) Times New Roman, (中文) +西文正文 (Calibri) 设置了格式: 字体: (中文) +西文正文 (Calibri)